Analysis as Interpretation: Interaction, Intentionality, Invention - GUCK, MARION A. (Music Theory Spectrum, 2006)
This essay advocates analysis of the human-music interaction that articulates what the music does to or for someone (e.g., that it confuses, astonishes, or moves a listener), and how it does so. To connect analysis to musical sensibility, I reframe it as interpretation in the everyday sense in which things are "open to interpretation," or in which an interpretation is an account of something that might be taken in a number of ways. I draw together four ideas under this umbrella; analysis as: (1) a meeting between an individual and some music; (2) a characteristic expression of its author; (3) experiences with music; and (4) conceptual and verbal invention.What I advocate might also be called a humanistic psychology of music.